Renewable Energy, Foreign Direct Investment and Sustainable Development: An Empirical Evidence - Parab, Narayan; Naik, Ramashanti; Reddy, Y. V. (International Journal of Energy Economics and Policy, 2020)
Renewable energy is replenished on a human timescale. The concern for the use of renewable energy is growing across the globe due to depleting non-renewable sources and various environmental issues. We construct a model of sustainable development to demonstrate the causality and co-integration between FDI inflows and renewable energy consumption. We consider data of select 43 countries for the period 2005 to 2017 and apply panel data analysis. The results reveal a unidirectional causality from renewable energy consumption to FDI inflows and the presence of a long-run relationship. Consequently, the constructed model will assist the government, non-government organizations, and companies in evaluating the significance of renewable energy and FDI inflows in sustainable development. Keywords: Renewable Energy, Foreign Direct Investment, Sustainable Development, Causation Effect, Co-integration JEL Classifications: Q2, F14, F21, F23 DOI: https://doi.org/10.32479/ijeep.10206